Back to Freud: A radicalism recalled* - Bloom, Leonard (PINS-Psychology in Society, 2026)
I intend in this paper to review Freud’s understanding of human psychology, and to remind both psychoanalysts and main-stream psychologists of its essentially radical approach. The psychological process with which Freud was concerned is more complicated than the shrivelled thing described and studied by behavioural scientists. I believe, too, that Freud’s style, with its subversive vein of social and intellectual anti-authoritarianism is another facet of his radicalism. Even now, psychoanalysis is opposed because of its power to strip the pretensions from the complacent conservatism of the political right and left, both in public life and in the soi-disant social sciences. The paper will introduce some points of divergence between main-stream behaviourist and cognitive psychologies (on the one hand) and psychoanalysis (on the other). This will lead into a discussion of Freud’s basic insights into human psychology. I then examine Freud’s psychobiological assumptions, and suggest that these, far from being conservative, offer an anti-racist and progressive biological understanding of human nature. The relevance of psychoanalysis to the problem of human freedom is next evaluated, and finally, I shall illustrate Freud’s essential radicalism from the humanist-psychoanalytic approach of Erich Fromm.